Effects of electroacupuncture on urinary metabolome and microbiota in presenilin1/2 conditional double knockout mice - Gao, Jie; Zhou, Nian; Lu, Mengna; Wang, Qixue; Zhao, Chenyi; Wang, Jian; Zhou, Mingmei; Xu, Ying (Frontiers in Microbiology, 2023)
Aims: The treatment of Alzheimer's disease (AD) is still a worldwide problem due to the unclear pathogenesis and lack of effective therapeutic targets. In recent years, metabolomic and gut microbiome changes in AD patients have received increasing attention, and the microbiome-gut-brain (MGB) axis has been proposed as a new hypothesis for its etiology. Considering that electroacupuncture (EA) efficiently moderate cognitive deficits in AD and its mechanisms remain poorly understood, especially regarding its effects on the gut microbiota, We performed urinary metabolomic and microbial community profiling on EA-treated AD model mice, presenilin1/2 conditional double knockout (PS cDKO) mice, to clarify the potential mechanism of EA treatment. Materials and methods: After 30 days’ EA treatment, recognition memory ability of PS cDKO mice was evaluated by Y maze and Novel object recognition task. Urinary metabolomic profiling were conducted with the untargeted GC-MS method, and 16S rRNA sequence analysis was applied to analyse microbial community. Besides, the association between differential urinary metabolites and gut microbiota was clarified by Spearman’s correlation coefficient analysis. Key findings: Besides reversed cognitive deficits, urinary metabolome and gut microbiota of PS cDKO mice were altered as a result of EA treatment. Notably, the increased level of isovalerylglycine and the decreased level of glycine and threonine in urine of PS cDKO mice were reversed by EA treatment, which are involved in glyoxylate and dicarboxylic acid metabolism, as well as glycine, serine and threonine metabolism. In addition to significantly enhancing the diversity and richness of the microbial community, EA treatment significantly increased the abundance of the genus Mucispirillum, while displaying no remarkable effect on the other major altered gut microbiota in PS cDKO mice, norank_f_Muribaculaceae, Lactobacillus, and Lachnospiraceae_NK4A136. There was a significant correlation between differential urinary metabolites and differential gut microbiota. Significance: EA alleviates cognitive deficits in AD by modulating gut microbiota and metabolites. Mucispirillum might play an important role in the underlying mechanism of EA treatment. Our study provides a reference for the future treatment of AD from MGB axis.